1997
DOI: 10.1002/(sici)1097-0142(19970701)80:1<75::aid-cncr10>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The results of intraoperative consultations in 181 ductal carcinomas in situ of the breast

Abstract: respectively. Sampling error was the main reason for the low detection rate, and technical inadequacy was a major factor contributing to interpretive problems. In multivariate regression analysis, FS accuracy was significantly associated with the clinical presentation of a palpable mass (odds ratio [OR] Å 4.16, 95% confidence interval [CI]: 2.04-8.45), the macroscopic finding of a mass (OR Å 3.03, 95% CI: 1.45-6.67), and necrosis (OR Å 3.13, 95% CI: 1.4-6.67). CONCLUSIONS.The authors concluded that the accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Adipose tissue in particular can be challenging to cut for frozen section analysis, often leading to tissue fragmentation and folding, or an increase in thickness. Given the technical limitations in quality and diagnostic utility, several studies have found false negative rates as high as 36% for frozen sections compared to permanent FFPE sections in certain procedures such as radical prostatectomy and breast-conserving surgery [44][45][46] . In many cancer types, concordance between frozen sections and permanent sections is high, but some cancer types such as melanoma show poor agreement 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue in particular can be challenging to cut for frozen section analysis, often leading to tissue fragmentation and folding, or an increase in thickness. Given the technical limitations in quality and diagnostic utility, several studies have found false negative rates as high as 36% for frozen sections compared to permanent FFPE sections in certain procedures such as radical prostatectomy and breast-conserving surgery [44][45][46] . In many cancer types, concordance between frozen sections and permanent sections is high, but some cancer types such as melanoma show poor agreement 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Although frozen section examinations have been described by many authors as a reliable method, it is nevertheless important to stress that its accuracy depends on multiple factors such as the indication, the organ, the precise anatomic site of the lesion, the quality of the material to be examined, the quality of the slides, and the experience of the technician and the pathologist 1–8 , 12 . Depending on the specialization of the ‘submitting’ hospitals, some pathology departments receive more or less specimens of a specific organ.…”
Section: Discussionmentioning
confidence: 99%
“…intraluminal benign vs. malignant epithelial proliferations or glandular typical vs. atypical hyperplasia) 21 , 24 , 27 , 28 . The accuracy of frozen section in the diagnosis of borderline non‐invasive or preinvasive breast lesions is uncertain 3 . Also, the combined interpretation of macroscopic and microscopic examinations of fresh breast biopsies is important and knowledge of all relevant clinical data is crucial 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional alternatives to FFPE H&E histopathology exist to offer rapid assessment of margin status while the patient remains in the surgical suite, though they suffer from limitations in technical quality and diagnostic accuracy in some applications 3 7 . Frozen section analysis (FSA) can generate slides available for brightfield microscopy in approximately 20 mins, which is considerably faster than FFPE permanent sectioning.…”
Section: Introductionmentioning
confidence: 99%